Analisa Perbandingan Portofolio Optimal Yang Terbentuk Dengan Menggunakan Beta Historis Dan Beta Koreksi Blume - , Riza Agus Irfanny ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to study the optimal portfolio comparisons are made using historical beta and beta correction Blume on the concept of Single Index Model for the banking industry. This is done by analyzing the results of optimal portfolios using historical beta and the optimal portfolio using the beta correction Blume. Optimal portfolio results were then compared and tested statistically using the T test to determine whether significant differences in the resulting optimal portfolios using historical beta and beta correction Blume The results of the analysis, the optimal portfolio using the beta correction Blume generate average profits are higher than the average profits generated by the historical beta. Further differences in the average gain was tested using the test statistic T and obtained an average yield of the advantages of using historical beta and beta Blume correction did not differ significantly Use of beta Blume correction to adjust the historical beta values for the formation of an optimal portfolio can be ignored for Investment Managers and stock anaylst in decision making